COPING STRATEGIES OF MINISTERS IN DEALING WITH DUAL ROLE CONFLICTS AT THE GTDI CHURCH IN LUMBAN TONGATONGA VILLAGE - Lastiur Batubara; Risydah Fadilah; Ummu Khuzaimah (SOSIOEDUKASI, 2026)
This study aims to describe the dual role conflict experienced by church ministers, its impact on their ministry and work roles, and the coping strategies used to deal with this conflict. This study uses a qualitative approach with a descriptive method. The research subjects consisted of two church ministers at the Church of God in Indonesia (GTDI) Lumban Tonga-tonga who also had roles as professional workers and family members. Data collection techniques were conducted through in-depth interviews, observation, and documentation. The results showed that dual role conflict manifested in the form of time constraints, emotional pressure, and differences in behavioural demands between work, church ministry, and family roles. This conflict has an impact on the effectiveness of ministry, work performance, and the psychological condition of the subjects. To overcome dual role conflict, the subjects developed various coping strategies, including time management, prioritisation, communication with relevant parties, social support from family and fellow ministers, and spiritual strengthening through prayer and reflection on faith. These coping strategies help subjects maintain role balance and continuity of service amid the various role demands they face. This study provides an understanding of the dynamics of dual role conflict among church ministers and the importance of coping strategies in maintaining balance between ministry, work, and family life.